Prognostic value of KRAS genotype in metastatic colorectal cancer (MCRC) patients treated with intensive triplet chemotherapy plus bevacizumab (FIr-B/FOx) according to extension of metastatic disease - Bruera Gemma; Cannita Katia; Di Giacomo Daniela; Lamy Aude; Troncone Giancarlo; Dal Mas Antonella; Coletti Gino; Frébourg Thierry; Sabourin Jean; Tosi Mario; Ficorella Corrado; Ricevuto Enrico (BMC Medicine, 2012)
Abstract Background Bevacizumab (BEV) plus triplet chemotherapy can increase efficacy of first-line treatment of metastatic colorectal cancer (MCRC), particularly integrated with secondary liver surgery in liver-limited (L-L) patients. The prognostic value of the KRAS genotype in L-L and other or multiple metastatic (O/MM) MCRC patients treated with the FIr-B/FOx regimen was retrospectively evaluated. Methods Tumoral and metastatic samples were screened for KRAS codon 12 and 13 and BRAF mutations by SNaPshot and/or direct sequencing. Fit MCRC patients <75 years were consecutively treated with FIr-B/FOx regimen: weekly 12-h timed flat-infusion/5-fluorouracil (TFI 5-FU) 900 mg/m2, days 1, 2, 8, 9, 15, 16, 22 and 23; irinotecan (CPT-11) 160 mg/m2 plus BEV 5 mg/kg, days 1, 15; oxaliplatin (OXP) 80 mg/m2, days 8, 22; every 4 weeks. MCRC patients were classified as L-L and O/MM. Activity and efficacy were evaluated and compared using log-rank test. Results In all, 59 patients were evaluated: 31 KRAS wild-type (53%), 28 KRAS mutant (47%). At 21.5 months median follow-up, objective response rate (ORR), progression-free survival (PFS) and overall survival (OS) were, respectively: KRAS wild-type 90%, 14 months, 38 months; KRAS mutant 67%, 11 months, 20 months. PFS and OS were not significantly different. PFS and OS were significantly different in L-L compared to O/MM evaluable patients. In KRAS wild-type patients, clinical outcome of 12 L-L compared to 18 O/MM was significantly different: PFS 21 versus 12 months and OS 47 versus 28 months, respectively. In KRAS mutant patients, the clinical outcome of 13 L-L compared to 14 O/MM was not significantly different: PFS 11 months equivalently and OS 39 versus 19 months, respectively. Conclusions The KRAS genotype wild-type and mutant does not significantly affect different clinical outcomes for MCRC patients treated with the first-line FIr-B/FOx intensive regimen. KRAS wild-type patients with L-L disease may achieve a significantly prolonged clinical outcome due to integration with secondary liver surgery, with respect to KRAS mutant patients.